Profiles and risk assessment of antibiotic resistome between Qinghai-Xizang Plateau and polar regions - Zhenzhe Wu; Guannan Mao; Yuan Gou; Mukan Ji; Qingqing Ma; Yongqin Liu (Geography and Sustainability)
Antibiotic resistance genes (ARGs) are increasingly recognized as a global public health threat, with glaciers acting as reservoirs for ARGs transported via atmospheric pathways. Warming climate accelerates glacier melting, releasing ARGs into downstream environments, posing ecological health and sustainable aquatic ecosystem development challenges. However, the distribution profiles of ARGs and their risks in glaciers from the polar region remain unclear. This study used 294 metagenomic sequences to investigate the distribution and risks of ARGs in glaciers across the Qinghai-Xizang Plateau, Antarctica, and the Arctic regions and compared them with adjacent and anthropogenically impacted environments. Among the three glacier regions studied, the Qinghai-Xizang Plateau exhibited the highest abundance of ARGs, whereas Antarctica displayed the lowest. ARG abundance in adjacent environments was comparable to that in the glaciers of the Qinghai-Xizang Plateau, but in the anthropogenically impacted environment, it was significantly higher than in glaciers. A shared resistome was identified in glaciers, dominated by bacitracin, multidrug, and macrolide-lincosamide-streptogramin (MLS) resistance genes. The bacA gene, which is related to bacitracin resistance, was the most common subtype, indicating that it is naturally present in microbial communities of glaciers. Risk assessments showed that 74.1 %–78.9 % of ARGs were low-risk in the Qinghai-Xizang Plateau and polar glaciers, indicating minimal human influence. However, 7.3 %–8.0 % were classified as high-risk, posing potential threats through horizontal gene transfer (HGT) and the spread of multidrug-resistant pathogens. These findings highlight the need to monitor ARGs in glacier environments, as climate change accelerates glacier melting and subsequent release of ARGs into downstream ecosystems.